Research hotspots and future trends in sepsis-associated acute kidney injury: a bibliometric and visualization analysis - Chen, Xing-Yue; Zhi, Li-Jia; Chen, Jun; Li, Rong; Long, Kun-Lan (Frontiers in Medicine, 2025)
ObjectivesSepsis-associated acute kidney injury (SA-AKI) commonly occurs in critically ill patients and is closely associated with adverse outcomes. A comprehensive analysis of the current research landscape in SA-AKI can help uncover trends and key issues in this field. This study aims to provide a scientific basis for research directions and critical issues through bibliometric analysis.MethodsWe searched all articles on SA-AKI indexed in the SCI-Expanded of WoSCC up to May 7, 2024, and conducted bibliometric and visual analyses using bibliometric software CiteSpace and VOSviewer.ResultsOver the past 20 years, there has been a steady increase in literature related to renal repair following AKI. China and the United States contribute over 60% of the publications, driving research in this field. The University of Pittsburgh is the most active academic institution, producing the highest number of publications. J. A. Kellum is both the most prolific and the most cited author in this area. “Shock” and “American Journal of Physiology-Renal Physiology” are the most popular journals, publishing the highest number of articles. Recent high-frequency keywords in this field include “septic AKI,” “mitochondrial dysfunction,” “inflammasome,” “ferroptosis,” and “macrophage.” The terms “mitochondrial dysfunction,” “inflammasome,” “ferroptosis,” and “macrophage” represent current research hotspots and potential targets in this area.ConclusionThis is the first comprehensive bibliometric study to summarize the trends and advancements in SA-AKI research in recent years. These findings identify current research frontiers and hot topics, providing valuable insights for scholars studying SA-AKI.